A Case Study on Hydrogen Fuel - Nakkeeran, S. (International Journal of Psychosocial Rehabilitation, 2019)
The degrading of the air quality resulting from the emissions of the existing energy conversion devices, in addition to the recent instability of the oil prices forced the need to a more stable zero-emission distribution generation technology or combination of technologies which allows a clean, cost effective supply of energy, on demand on a large scale and in any location. Thus, renewable energy generation or the decentralized power systems like wind, photovoltaic, as well as new hydrogen and fuel cells technologies are developing nowadays to take over from fossil hydrocarbons combustion. Fuel cell is an emerging technology which could allow a clean, cost effective supply of energy on demand on a large scale and in any location. This paper will act as a literature survey to the fuel cell technology. It will introduce the different fuel cell types with their advantages and disadvantages, and their suitability for different applications. It will also discuss the technical and economic issues facing the spread of this technology, and how to move to a worldwide hydrogen technology. It will also brief the current state of fuel cells with both drivers and barriers to its market growth. Further recommended work for the advance and spread of use of the fuel cells will be also highlighted.